From the concept of “good death” in the ancient world to the modern concept of “euthanasia” - Montaguti, Elena; Jox, Ralf; Zwick, Elisabeth; Picozzi, Mario (Medicina Historica, 2018)
Introduction: This article was born with the intention of analyzing the concept of “good death” and more specifically that of “euthanasia” within classical literature and early Christianity, in order to understand the term’s evolution during the course of history and how it is understood today. Methods: The first part of this article will analyze the concept of "good death" in epic poetry and respectively the ideal of Kalokagathia in epic poetry and in historiography. This research will cover many centuries. The focus of the central section of this research will be on the concept of “good death” in Plato, as well as in two of the most important philosophical schools of antiquity: Epicureanism and Stoicism. Related to this last aspect, our attention is directed to Seneca, the representative of Roman Stoicism under the emperor Nero. An interesting article on the comparison between the Gospel of Paul, Stoicism and the fourth book of the Maccabees about the concept of "good death" gave me the incentive to deepen an agonistic metaphor deriving from the sporting environment in the ancient world. The study of “good death” conducted by the Church Fathers allows a better understanding of how the treated concept has assumed a value from Christianity through many changes. The third and final part analyzes how the concept of death is used in our day and starting from when the term “euthanasia” appeared. Objective: This study aims to clarify how some modern concepts are often linked to the ancient world; for example, the concept of today’s euthanasia and of assisted death did not exist in antiquity in the same sense as modern interpretation. Conclusions: The end of life analysis reveals a variety of values about the concept of “good death” in different time periods and cultures. The research on “good death” and on assisted death is well linked to the theme concerning the quality of life. This is one of the most important topics in palliative medicine, a field that is becoming increasingly important and is related to the well-being of the patient.